2021
DOI: 10.1016/j.econmod.2020.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Financial spillovers and spillbacks: New evidence from China and G7 countries

Abstract: With the increasing openness of the Chinese economy, Chinese financial markets are becoming more integrated with those in developed markets. The goal of this paper is to comprehensively investigate the spillovers and spillbacks in stock, bond, and foreign exchange markets between China and the G7 countries using data from 2000 to 2018. Four important findings emerge: (1) financial spillovers account for a large proportion of the variations in bond, stock, and foreign exchange markets, indicating that the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…At this stage of the pattern, China’s financial system has entered a new period full of volatility and uncertainty after the long-term accumulation of systemic risks. In keeping with the findings from the research of Fang et al [ 2 ], with the increasing openness of the Chinese economy, Chinese financial markets are becoming more integrated with those of developed markets, and Chinese financial markets are demonstrating a growing impact on global financial markets over time, especially during periods of turbulence.…”
Section: Introductionsupporting
confidence: 67%
“…At this stage of the pattern, China’s financial system has entered a new period full of volatility and uncertainty after the long-term accumulation of systemic risks. In keeping with the findings from the research of Fang et al [ 2 ], with the increasing openness of the Chinese economy, Chinese financial markets are becoming more integrated with those of developed markets, and Chinese financial markets are demonstrating a growing impact on global financial markets over time, especially during periods of turbulence.…”
Section: Introductionsupporting
confidence: 67%
“…, 2021). Fang et al. (2021) found that the impact of Chinese financial markets become more important on global financial markets over time, especially during periods of turbulences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We also employ multivariate copula to model the dependency structure of the East-Asian and the US stock markets. The dependency structures are used to identify risk spillovers ( Adrian & Brunnermeier, 2016 ; Fang et al, 2021 ; Shahzad et al, 2021 ). The robustness of the spillover effect is verified through the bootstrap Kolmogorov-Smirnov (KS) test used by several scholars ( Bernal et al, 2014 ; Reboredo & Ugolini, 2015 ).…”
Section: Introductionmentioning
confidence: 99%